假定A为自变量,B为因变量,弹性的数学表达式为()
A: E=(AA/A·(B/
B: E=(AB/A·(A/
C: E=(AB/·(△A/
D: E=(B/A·(A/△
A: E=(AA/A·(B/
B: E=(AB/A·(A/
C: E=(AB/·(△A/
D: E=(B/A·(A/△
举一反三
- 假定A为自变量,B为因变量,弹性的数学表达式为() A: E=(AA/A·(B/ B: E=(AB/A·(A/ C: E=(AB/·(△A/ D: E=(B/A·(A/△
- 假定A为自变量,B为因变量,弹性的数学表达式为() A: E=(AA/A B: ·(B/ C: D: E=(AB/A E: ·(A/ F: G: E=(AB/ H: ·(△A/ I: J: E=(B/A K: ·(A/△ L:
- 假定A为自变量,B为因变量,弹性的数学表达式为() A: E=(AA/AB.·(B/A. B: E=(AB/AA.·(A/B. C: E=(AB/B.·(△A/A. D: E=(B/AB.·(A/△A.
- 假定A为自变量,B为因变量,弹性的数学表达式为 A: E=(ΔB/ΔA)/(A/B) B: E=(ΔA/ΔB)/(B/A) C: E=(ΔB/B)/(ΔA/A) D: E=(B/ΔB)/(A/ΔA)
- 假定A为自变量,B为因变量,弹性的数学表达式为() A: E=(ΔA/ΔB).(B/A) B: E=(ΔB/ΔA).(A/B) C: E=(ΔB/B).(ΔA/A) D: E=(B/ΔB).(A/ΔA)